PESANTREN DAN KONSERVASI LINGKUNGAN (STUDI KASUS DI PONDOK PESANTREN DARUMUHYIDDIN NW LOMBOK TIMUR ) - Munawir Sazali (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2023)
Abstract: This study aims to reveal a model of environmental education that is observed from the aspect of Islamic values. Efforts to promote environmental awareness through environmental education will go a long way in preventing the destruction of new environments and even repairing the damage that has already been done. Environmental education is an effort to develop and increase public awareness to behave well towards the environment so that the sustainability of the ecosystem is maintained. This research method is qualitative with the existing model phenomenology. Research Place in Darumuhyiddin NW Debok Islamic Intervention. Collecting data using interviews, document studies, and participatory observations. Data analysis is done by reducing data, displaying data, and verifying. The results of the study reveal environmental education activities that transform religious moral values ??in relation to the designation of Islamic boarding schools, until before the 1960s the term